BUSINESS INTELLIGENCE: KONSEP DAN METODE - Darudiato, Suparto; Santoso, Sigit Wisnu; Wiguna, Setiady (CommIT (Communication and Information Technology) Journal, 2010)
Recently, usage of Information Technology (IT) as assisting tools in business activities is becoming more common. Business transactions are conducted with support of IT tools so that they can be well processed by system. This is only a small part of IT usage in supporting business activities. IT role can be increased by designing and implementing a system which can extract and change business information from existing operational data so that in the end it can give support in formulating business decisions. This research will discuss the concept, benefits, categories, and method of Business Intelligence implementation.Keywords: business intelligence, method, balanced scorecard